2008
DOI: 10.1016/j.ajog.2008.09.870
|View full text |Cite
|
Sign up to set email alerts
|

The clinical content of preconception care: genetics and genomics

Abstract: The prevalence of paternal and maternal genetic conditions that affect pregnancy varies according to many factors, including parental age, medical history, and family history. While some genetic conditions that affect pregnancy are easily identified early in life, others are not and may require additional diagnostic testing. A complete three-generation family medical history that includes ethnicity information about both sides of the family is arguably the single best genetic “test” applicable to preconception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…4,5 It is indeed widely recognized that preconception interventions are most effective in managing and reducing reproductive risks and warrant a proactive strategy to maximize their potential impact. 11 Other original results of our study are worth mentioning. The percentage of newly identified genetic risks was similar in Italian and non-Italian women.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…4,5 It is indeed widely recognized that preconception interventions are most effective in managing and reducing reproductive risks and warrant a proactive strategy to maximize their potential impact. 11 Other original results of our study are worth mentioning. The percentage of newly identified genetic risks was similar in Italian and non-Italian women.…”
Section: Discussionmentioning
confidence: 81%
“…During pregnancy significant organizational challenges are faced, and higher resource consumption and lower counselors' satisfaction may be observed . It is indeed widely recognized that preconception interventions are most effective in managing and reducing reproductive risks and warrant a proactive strategy to maximize their potential impact …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only 28% of physicians who offered genetic screening/testing indicated that family history was a factor that influenced their decision. Our respondents may have interpreted the vignette to suggest that the patient’s family history of genetic disorders was negative, but these findings still highlight that emphasis of family history as a powerful risk assessment tool and indicator for genetic testing is needed [33,34]. Finally, our results also speak to the need to clarify existing guidelines for carrier screening, both in terms of how they describe targeted population groups and how they are interpreted and applied by physicians.…”
Section: Discussionmentioning
confidence: 91%
“…Parents of patients with rare diseases may be at risk of genetic diseases or other problems that require accurate evaluation and a tailored preconception counseling [20]. We recently conducted a study on the validity and reliability of web information on preconception recommendations in which we found that valid and complete information is rarely found on the web [21].…”
Section: Discussionmentioning
confidence: 99%